Nonequilibrium spin dynamics in the chiral soliton lattice host YbNi3Al9 - Yamei Wang; Haonan Jin; Jiefeng Cao; Rui Yu; Junqin Li; Wei Tong; Junmin Xu; Fangyuan Zhu; Yong Wang; Lei Zhang; Renzhong Tai (Results in Physics)
The uniaxial chiral magnetic material YbNi3Al9 is proposed as a host for a chiral soliton lattice (CSL). In this study, we thoroughly investigate the spin dynamics in YbNi3Al9 single crystals using magnetization (M)-relaxation and electron spin resonance (ESR) techniques. The M-relaxation analysis clearly reveals characteristics of a nonequilibrium CSL in YbNi3Al9. A prolonged relaxation is observed in the highly-nonlinear-CSL state, indicating nonequilibrium spin dynamics during the annihilation or nucleation of chiral magnetic solitons, consistent with the unfrustrated magnetic cluster model. The ESR study shows significant microwave responses when the magnetic field is applied perpendicular to the c-axis (H⊥c), while a weak response is observed when the field is aligned with the c-axis (H//c). Two resonance lines are identified for H⊥c. The resonance signal at lower fields is attributed to the Goldstone excitation of chiral magnetic solitons, while the signal at higher fields is associated with ferromagnetic resonance. These findings enhance our understanding of the nonequilibrium spin dynamics of the CSL in YbNi3Al9 single crystals and are beneficial for the application of chiral magnetic solitons in spintronics.